Structural and functional network characteristics and facility delivery among women in rural Ghana - Leslie E. Cofie; Clare Barrington; Kavita Singh; Sodzi Sodzi-Tettey; Susan Ennett; Suzanne Maman (BMC, 2017)
Abstract Background Health facility births contribute to the prevention of maternal deaths. Although theoretical and empirical evidence suggest that social network characteristics influence facility delivery, examination of this relationship in sub-Saharan Africa is limited. We determined whether network structural and functional characteristics were associated with, or had an interactive effect on health facility delivery in rural Ghana. Methods Data on mothers (n = 783) aged 15-49 years came from a Maternal and Newborn Health Referral (MNHR) project in Ghana, and included egocentric network data on women's social network characteristics. Using multivariate logistic regression we examined the relationship between facility delivery and women's network structure and functions, as well as the interaction between network characteristics and facility delivery. Results Higher levels of instrumental support (e.g. help with daily chores or seeking health care [OR: 1.60, CI: 1.10-2.34]) and informational support (OR: 1.66, CI: 1.08-2.54) were significantly associated with higher odds of facility delivery. Social norms, such as knowing more women who had received pregnancy-related care in a facility, were significantly associated with higher odds of facility delivery (OR: 2.20, CI: 1.21-4.00). The number of network members that respondents lived nearby moderated the positive relationship between informational support and facility delivery. Additionally, informational support moderated the positive relationship between facility delivery and the number of women the respondents knew who had utilized a facility for pregnancy-related care. Conclusions Social support from network members was critical to facilitating health facility delivery, and support was further enhanced by women's network structure and norms favoring facility delivery. Maternal health interventions to increase facility delivery uptake should target women's social networks.